Solve: 2(−n−3)−7(5+2n)
Mathematics
saffanaa2006
Question
Solve:
2(−n−3)−7(5+2n)
2(−n−3)−7(5+2n)
2 Answer

1. User Answers Anonym
Answer:
−16n−41
Explanation
Distribute:
=(2)(−n)+(2)(−3)+(−7)(5)+(−7)(2n)
=−2n+−6+−35+−14n
Combine Like Terms:
=−2n+−6+−35+−14n
=(−2n+−14n)+(−6+−35)
=−16n+−41

2. User Answers lordsonmyk
Answer:
16n41
Stepbystep explanation:
2(n3)7(5+2n)
First begin by expanding the bracket. That is, multiplyingthe brackets by 2 and 7 appropriately.
In doing so we have,
2(n) x 2(3) 7(5) x 7 (+2n)
simplifying becomes:
2n63514n
collwct like terms becomes 2n14n635
Final answer becomes Thus: 16n41